Death of the Grand Duke Konstanty Pawłowicz during the cholera epidemic in Vitebsk in 1831 - Janicka, Iwona (Requiem, 2025)
As a result of the outbreak of the November Uprising, Grand Duke Konstanty Pavlovich and his wife, Duchess Joanna Grudzińska of Łowicz, were forced to leave Warsaw. He went to Vitebsk, where there had been a cholera epidemic since 5 June 1831. He stayed in the city for just twelve days (from 15 June) and it was here that he most probably contracted the disease. His sudden death on 27 June prompted rumours of his alleged poisoning by Count Aleksei Fyodorovich Orlov, and even doubts as to whether he had actually died. In fact, the cause of death was cholera. His body was embalmed and accompanied by a modest procession, moved to the temple. The place was hastily and carelessly prepared. It was only a few days later that its decoration was improved. The Grand Duke was bid farewell twice - in June in Vitebsk and then in August in St Petersburg. A detailed description of the first ceremony can be found in the ‘Commemorative book of the Vitebsk gouvernement for 1864’. According to the source, the funeral procession was attended by numerous representatives of the prince’s court, the military, clergy of various denominations and representatives of the municipal authorities, schools and other institutions. The ceremonialist forbade Jews from taking part in the ceremony. The coffin on its way first to Gatczyna and then to St Petersburg was accompanied by the Grand Duke’s wife, Joanna Grudzinska.